2021
DOI: 10.1371/journal.pntd.0009313
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a human-serum-based in vitro growth method for drug screening on juvenile development stages of Schistosoma mansoni

Abstract: Background Schistosomiasis affects over 200 million people worldwide but only praziquantel is available for treatment and control. Drug discovery is often based on phenotypic drug screening, involving different parasite stages retrieved from infected mice. Aiming to reduce animal use, we validated an in vitro growth method for juvenile Schistosoma mansoni for the purpose of drug sensitivity assays. Methodology/Principal findings We compared inter–batch variability of serum, worm size and organ development, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Schistosomiasis treatment relies mainly on PZQ, which despite having high potency against all species of Schistosoma spp., can present very low efficacy against some life stages of the worm such as 3 to 4-week old larva (Doenhoff et al, 2008), slowing down the eradication of schistosomiasis in endemic areas requiring repeated mass treatments in the same population (Fenwick and Webster, 2006;Melman et al, 2009;Crellen et al, 2016;da Silva et al, 2017). In the context of in vitro drug screening, a more recent publication showed that juvenile stages developed in vitro and in vivo have similar sensitivity to PZQ when treated in vitro (Buchter et al, 2021), which gives support to the methodology used here. Based on that, candidate lead compounds that show efficacy against schistosomula and/or at least one adult worm sex can be explored to support schistosomiasis treatment, while those that target only the larval stages can be developed for use in combination with PZQ.…”
Section: Discussionsupporting
confidence: 70%
“…Schistosomiasis treatment relies mainly on PZQ, which despite having high potency against all species of Schistosoma spp., can present very low efficacy against some life stages of the worm such as 3 to 4-week old larva (Doenhoff et al, 2008), slowing down the eradication of schistosomiasis in endemic areas requiring repeated mass treatments in the same population (Fenwick and Webster, 2006;Melman et al, 2009;Crellen et al, 2016;da Silva et al, 2017). In the context of in vitro drug screening, a more recent publication showed that juvenile stages developed in vitro and in vivo have similar sensitivity to PZQ when treated in vitro (Buchter et al, 2021), which gives support to the methodology used here. Based on that, candidate lead compounds that show efficacy against schistosomula and/or at least one adult worm sex can be explored to support schistosomiasis treatment, while those that target only the larval stages can be developed for use in combination with PZQ.…”
Section: Discussionsupporting
confidence: 70%
“…This is consistent with the low percentage (ranging from 10% to 15%) of IVLE that hatch fully viable and infectious miracidia ( 24 ). Recent improvements in culture conditions offer novel and informative approaches to sustain and study in vitro and ex vivo parasite development, including sexual differentiation and fecundity ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the low percentage (ranging from 10% to 15%) of IVLE that hatch fully viable and infectious miracidia (Mann et al, 2011). Recent improvements on culture conditions offer novel and informative approaches to sustain and study in vitro and ex vivo parasite development, including sexual differentiation and fecundity (Wang et al, 2019;Anisuzzaman et al, 2021;Buchter et al, 2021).…”
Section: Discussionmentioning
confidence: 53%